Forecast Analysis Towards Golden Indonesia 2045 - Purba, Switamy Angnitha; Tampubolon, Ferdinan Rinaldo; Sitinjak, Anna Angela; Simarmata, Justin Eduardo; Sirait, Debora Exaudi (Journal of Research in Mathematics Trends and Technology, 2026)
The year 2045 marks 100 years since Indonesia gained its independence. The government's vision for that year is Golden Indonesia 2045. In the final draft of the 2025-2045 RPJPN of the Ministry of National Development Planning / Bappenas there are five main targets of the 2045 Golden Indonesia Vision. In this article, a forecast is conducted using the Least Square method to determine whether Indonesia can achieve this vision by 2045. There are 8 aspects that will be forecasted which are considered to represent the five targets of Golden Indonesia 2045. The eight aspects are Human Development Index; Information and Communication Technology Development Index; Per Capita Income Data; Poverty Rate; Open Unemployment Rate; National Road Stability; Provincial Road Stability; and District and City Road Sustainability.